On the Controversies of Democratic Pluralism: Discursive Interpretations of the Socialist System Crisis in Bosnia and Herzegovina’s Youth Press at the End of the 1980s - Sabina Veladžić (Društvene i Humanističke Studije)
The paper examines so-called democratization period in Bosnia and Herzegovina at the end of the 1980s, during which the outbreak of the Agrokomerc affair and a series of other scandals led to political delegitimization of both the Bosnian and Herzegovinian communist leadership and the existing discursive regime of truth, paving the way for the affirmation of a new political and ideological paradigm as well as the emergence of new social and political power structures. The focus of this paper is on critiques in the youth press in Bosnia and Herzegovina from 1987 to 1990 directed toward the socialist political elite, which had already been experiencing disintegration and decline, as well as on interpretations of the Yugoslav and Bosnian crisis portrayed by the aformentioned press, becoming an integral part of that critique. The author, on one hand, shows that the identity and conceptual political platform of the analysed youth press was and remained Bosnian and civic. On the other hand, she points out that the ideological pluralism promoted by the Bosnian youth press as a value of democratization actually provided media space and legitimacy to the victims (in some cases self-declared), i.e. enemies of the socialist regime, being mostly nationalists, for their interpretations of national and past realities. In this sense, it partially aided the affirmation of national exclusivity as the new dominant ideological paradigm, which ultimately, through wartime violence, led to the disintegration of the Bosnian and Herzegovinian society into three closed national entities. All of this occurred within an underdeveloped civil society with insufficient recognition of the value of civic political projects, in addition to a discredited political left, an advanced process of national Sabina Veladžić On the Controversies of Democratic Pluralism: Discursive Interpretations of the homogenization as well as the political mobilization of the largest Yugoslav nation.